Teaching cooperative learning : the challenge for teacher education - Cohen, Elizabeth G., 1931-2005; Brody, Celeste M.; Sapon-Shevin, Mara (SUNY series in teacher preparation and development., 2004)
Annotation Teacher educators from ten institutions and programs in the United States, Canada, and Germany describe the ways in which they have changed teacher preparation to more fully incorporate cooperative learning concepts. Analytical commentaries on the programs highlight the learning experience of these programs as well as underlying issues of needed reforms in teacher education. Included among best practices in education, cooperative learning may require a shift in program philosophy and disciplinary areas to meet the challenge of complex organizations and diverse student populations. As the essays in the volume demonstrate, a new alignment of field experiences to provide support for novices to implement cooperative strategies, and to receive timely and effective supervision for these attempts, may also be required.